Physical approach for a quantitative analysis of the phytosterols in free phytosterol-oil blends by X-ray Rietveld method. (October 2019) - Gomes Silva, M.; Santos, V.S.; Fernandes, G.D.; Calligaris, G.A.; Santana, M.H.A.; Cardoso, L.P.; Ribeiro, A.P.B.
Abstract: This study investigates and compares the thermal phase transition and crystallization characteristics of a commercial food grade free phytosterol blend (FP) with a stigmasterol analytical standard (SS), the FP behavior in a food model system after its addition to high oleic sunflower oil (HOSO). The properties of the FP:HOSO blends were studied by differential scanning calorimetry, solid content, crystal morphology, and X-ray diffraction (XRD) measurements. The Rietveld method (RM) was applied associated with the XRD measurements to support phase analysis and the study of crystallinity degree. The materials were also characterized by means of chemical composition, such as fatty acids and triacylglycerol profiles, for HOSO, and phytosterol profile, for FP. Regarding phase behavior and crystallinity properties, FP has very similar characteristics to SS. The thermal behavior of FP:HOSO blends has two characteristic peaks, one from FP and the other from HOSO. The similarity reported in the literature between the diffraction pattern of FP and pure phytosterols is a positive characteristic for FP. A high FP concentration resulted in high supersaturation and thus the formation of small crystals. The incorporation of HOSO reduced of the large agglomeration of FP crystals and the dispersion crystalline aggregates (spherulites) of FP crystals. The application of RM in FP:HOSO blends to quantify the crystalline and amorphous phases was successfully used. The application has provided the expected value for these phases, according to the same experimental mass ratio of the blends, thereby validating the applicability of this approach in this type of material. Graphical abstract: Unlabelled Image Highlights: Blends of free phytosterols present thermal behavior and a crystalline phase similar to analytical standard phytosterol. The dispersion effect of HOSO into FP influences thermal phase transition for FP: HOSO (20:80) and FP: HOSO (10, 90) blends. HOSO contributes to the amorphous content in XRD pattern for the all FP:HOSO blends. The Rietveld method can be useful for an initial determination of the phytosterols content present in vegetable oil. The crystallite size increases with the increase of HOSO until the FP:HOSO (50:50) blend.